Survival Rate of Standard Implants in the Posterior Maxilla - Fahim Atamni; Valentin Topalo; Manal Atamni; Magde Atamni (Romanian Society of Oral Rehabilitation, 2010)
The present study evaluated standard implant survival and marginal bone loss in the posterior maxilla in a 2 stage-procedure based on retrospective study reporting on implants with a mean follow-up time of 1-10 years of functional loading. There were identified from a search of more than 10 years archive materials. The sample was composed of 126 patients (72 female and 54 males mean age 55) rehabilitated with 536 standard implants in the posterior maxilla between 1999 - 2008. The inclusion criteria were patients in good general health with residual bone height ≥ 10 mm of the posterior maxilla who had been rehabilitated with one to four implants. Second-stage surgery was performed in a mean of 4.3 months post implantation. Implant success was defined according to the criteria of Albrektsson et al. Not only the overall survival rate was analyzed but also the crestal bone loss 1 to 10 years of loading. Bone loss was measured on panoramic radiographs on the mesial and distal of each implant, and the largest value was selected as the bone loss. The influence of implants characteristics (type, length, diameter and coating) on implant failure and complication rates were evaluated. Patient satisfaction with the prosthesis were also evaluated. The total 10 years cumulative survival rate was 94% (32 implants were lost). The mean bone loss around implants in the posterior maxilla after 1 to 10 years of loading was 1.8 mm. All prosthesis of survival implants were stable at the end of observation period. Patients were satisfied with comfortable stability, esthetics and functionality of the prosthesis. Available indications suggest that implants placed in pristine sites enjoy the high long - term survival rates of dental implants.